Two-component carnitine monooxygenase from Escherichia coli: functional characterization, inhibition and mutagenesis of the molecular interface. Issue 9 (30th September 2022) - Piskol, Fabian; Neubauer, Kerstin; Eggers, Maurice; Bode, Lisa Margarete; Jasper, Jan; Slusarenko, Alan; Reijerse, Edward; Lubitz, Wolfgang; Jahn, Dieter; Moser, Jürgen
Abstract: Gut microbial production of trimethylamine (TMA) from l -carnitine is directly linked to cardiovascular disease. TMA formation is facilitated by carnitine monooxygenase, which was proposed as a target for the development of new cardioprotective compounds. Therefore, the molecular understanding of the two-component Rieske-type enzyme from Escherichia coli was intended. The redox cofactors of the reductase YeaX (FMN, plant-type [2Fe-2S] cluster) and of the oxygenase YeaW (Rieske-type [2Fe-2S] and mononuclear [Fe] center) were identified. Compounds meldonium and the garlic-derived molecule allicin were recently shown to suppress microbiota-dependent TMA formation. Based on two independent carnitine monooxygenase activity assays, enzyme inhibition by meldonium or allicin was demonstrated. Subsequently, the molecular interplay of the reductase YeaX and the oxygenase YeaW was addressed. Chimeric carnitine monooxygenase activity was efficiently reconstituted by combining YeaX (or YeaW) with the orthologous oxygenase CntA (or reductase CntB) from Acinetobacter baumannii . Partial conservation of the reductase/oxygenase docking interface was concluded. A structure guided mutagenesis approach was used to further investigate the interaction and electron transfer between YeaX and YeaW. Based on AlphaFold structure predictions, a total of 28 site-directed variants of YeaX and YeaW were kinetically analyzed. Functional relevance of YeaX residues Arg 271, Lys 313 and Asp 320 was concluded. Concerning YeaW, a docking surface centered around residues Arg 83, Lys 104 and Lys 117 was hypothesized. The presented results might contribute to the development of TMA-lowering strategies that could reduce the risk for cardiovascular disease.